Urgensitas Pemahaman “Kerusakan Manusia Sebagai Gambar Allah” Dalam Pelayanan Pastoral Konseling Bagi Warga Gereja - Nehemia Nome (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
This article uses the library research method. The research conducted is an attempt to describe the "Significance of Understanding Human Damage as the Image of God in Pastoral Counseling Services for Church Members". This research aims to contribute thoughts on the problems currently being experienced by some members of the church. The problem is, there are not a few church members who still do not maintain the divinity of God's attributes within them. Thus, the tendency that occurs is that church members act arbitrarily without realizing that they are the image and likeness of God; who has a role as a representative in this world in protecting and caring for His creation. So as an alternative problem solving, one of the most effective approaches is pastoral counseling services. Through the pastoral counseling service, church members must be educated and guided so that they realize that within themselves there are attributes of God that must be maintained with holiness. One of the ways is by avoiding various things that mix and are related to sin.